Pemahaman Makna Kata Bahasa Indonesia Terhadap Mahasiswa NTT Yang Menempuh Pendidikan di Unitomo Surabaya - Megawati Simanjuntak, Nensy; Adrianie, Melisya; Habadota, Nonrilla (Jurnal Pendidikan Tambusai, 2023)
Often understand the meaning of words and sentences in the everyday world with misunderstandings or mistakes that are considered always true. So that makes the word or the meaning of the Indonesian word itself wrong. Therefore this research is present as a justification for the correct meaning of words in accordance with the rules of the Indonesian language. This research is in the form of a quantitative descriptive research that uses the theory of field work with NTT students who are studying at UNITOMO Surabaya with different study programs. The data used is filling out a questionnaire with the title "Guess the correct Indonesian word questionnaire". overall total of 100 points. Below are examples of words that have been interpreted according to (KBBI) namely recreation, steadfast, imaginative, illegal, rector, julid, auditorium, bazaar, magnificent, and sidewalk. Only 9 words are considered correct according to the rules of the Big Indonesian Dictionary (KBBI). As for 1 question that is considered misguided or wrong in answering it. There are several factors that cause this meaning to be correct, namely (1) looking at the mass media in more detail, (2) listening from friends around (the community), looking at the meaning in the dictionary (3) it is often used as a discussion in the everyday world. Efforts to correct the meaning which is considered to be misguided is the way to answer it by correcting the Indonesian language dictionary and obliging the mass media to find out in more detail the meaning